Nutritional management and postoperative prognosis of newborns submitted to primary surgical repair of gastroschisis - Flavia Miranda da Silva Alves; Marcelo Eller Miranda; Marcos José Burle de Aguiar; Maria Cândida Ferrarez Bouzada Viana (Elsevier, 2016)
Abstract Objective Gastroschisis is a defect of the abdominal wall, resulting in congenital evisceration and requiring neonatal intensive care, early surgical correction, and parenteral nutrition. This study evaluated newborns with gastroschisis, seeking to associate nutritional characteristics with time of hospital stay. Methods This was a retrospective cohort study of 49 newborns undergoing primary repair of gastroschisis between January 1995 and December 2010. The newborns' characteristics were described with emphasis on nutritional aspects, correlating them with length of hospital stay. Results The characteristics that influenced length of hospital stay were: (1) newborn small for gestational age (SGA); (2) use of antibiotics; (3) day of life when enteral feeding was started; (4) day of life when full diet was reached. SGA infants had longer length of hospital stay (24.2%) than other newborns. The length of hospital stay was increased by 2.1% for each additional day taken to introduce enteral feeding. However, slower onset of full enteral feeding acted as a protective factor, decreasing length of stay by 3.6%. The volume of waste drained by the stomach catheter in the 24 h prior the start of enteral feeding was not associated with the timing of diet introduction or length of hospital stay. Conclusion Early start of enteral feeding and small, gradual increase of volume can shorten the use of parenteral nutrition. This management strategy contributes to reduce the incidence of infection and length of hospital stay of newborns with gastroschisis.